2022
DOI: 10.1038/s41387-022-00209-z
|View full text |Cite
|
Sign up to set email alerts
|

Is vascular insulin resistance an early step in diet-induced whole-body insulin resistance?

Abstract: There is increasing evidence that skeletal muscle microvascular (capillary) blood flow plays an important role in glucose metabolism by increasing the delivery of glucose and insulin to the myocytes. This process is impaired in insulin-resistant individuals. Studies suggest that in diet-induced insulin-resistant rodents, insulin-mediated skeletal muscle microvascular blood flow is impaired post-short-term high fat feeding, and this occurs before the development of myocyte or whole-body insulin resistance. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
(111 reference statements)
0
4
0
1
Order By: Relevance
“…Our research underscores the complex relationship between diet, insulin resistance, and anthropometric indicators. Unlike previous studies, which focused on short-term dietary interventions, our findings suggest the importance of sustained dietary patterns in managing insulin resistance [23,24]. This long-term perspective is crucial for developing effective dietary guidelines that go beyond temporary adjustments and foster enduring health improvements.…”
Section: Discussionmentioning
confidence: 59%
“…Our research underscores the complex relationship between diet, insulin resistance, and anthropometric indicators. Unlike previous studies, which focused on short-term dietary interventions, our findings suggest the importance of sustained dietary patterns in managing insulin resistance [23,24]. This long-term perspective is crucial for developing effective dietary guidelines that go beyond temporary adjustments and foster enduring health improvements.…”
Section: Discussionmentioning
confidence: 59%
“…The transcriptional activation of several genes linked to the inflammatory response is also caused by JNK1 and IKK, which leads to insulin resistance. JNK1 and IKK signalling DOI: http://dx.doi.org/10.5772/intechopen.107362 pathways are activated by the influx of more free fatty acids and glucose [9]. The transcription inflammation associated genes causes the phosphorylation and activation of IKK that further encourages the ubiquitination and destruction pathways in proteasome thereby translocating NF into the nucleus.…”
Section: Glucose Intolerance and Insulin Resistancementioning
confidence: 99%
“…Thus, our recent study demonstrated that metformin treatment improved (but did not fully correct) the microvascular response to insulin in an insulin-resistant cohort. This is important because current evidence has consistently demonstrated that microvascular insulin resistance coexists with metabolic insulin resistance (61,62) and emerging evidence suggests that targeting microvascular insulin resistance may be a critical component of any therapeutic strategy designed to prevent and/or reduce whole-body metabolic insulin resistance (61,63).…”
Section: Clinical Evidence Of Metformin's Microvascular Actionmentioning
confidence: 99%